HUBUNGAN PENGETAHUAN CUCI TANGAN YANG BAIK DAN BENAR DENGAN KEJADIAN COVID-19 DI PUSKESMAS PEMURUS DALAM KOTA BANJARMASIN - Salma Hanina; Farida Heriyani; Ira Nurrasyidah; Meitria Syahdatina Noor; Siti Washilah (Homeostasis, 2022)
Good and right handwashing is described as cleaning hands with soap and running water with the right steps. The aim of this study is to explain the association between good and correct handwashing knowledge with the happenings of COVID-19 in Pemurus Dalam Health Center at Banjarmasin City. This study uses analytic observational with a case control approach as research method. Cluster sampling is used as sampling method with the number of samples in each case and control group are 32 people who suits both inclusion and exclusion criteria. Method to claim the result of analysis of data in the research is using chi square test. Univariate analysis results showed that most respondents in the case group (65.62%) had poor knowledge about good and correct handwashing compared to the control group, which mostly had good knowledge (58.38%). Bivariate analysis test of the relationship between good and correct hand washing knowledge showed a p value of 0.045 with an OR value of 2.79